2015
DOI: 10.1080/08870446.2015.1045512
|View full text |Cite
|
Sign up to set email alerts
|

Psychological support needs of patients with head and neck cancer and their caregivers: A qualitative study

Abstract: The results of this study suggest that psychological interventions for patients with HNC and their caregivers should be delivered early after diagnosis in face to face sessions, presenting honest and factual information about the disease and coping strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 50 publications
4
56
0
2
Order By: Relevance
“…Other studies have reported that HNC caregivers have unmet informational and supportive care needs [22-25]. Similarly, the HNC caregivers in our study reported interest in stress reduction programs, cancer education, and classes on finances, caregiving, and personal well-being.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Other studies have reported that HNC caregivers have unmet informational and supportive care needs [22-25]. Similarly, the HNC caregivers in our study reported interest in stress reduction programs, cancer education, and classes on finances, caregiving, and personal well-being.…”
Section: Discussionsupporting
confidence: 75%
“…Among caregivers of HNC patients, moderate caregiving burden and poorer psychological health in comparison to patients and the general population have been reported [3, 21]. HNC caregivers have reported unmet informational needs related to the disease and treatment, patient side effects, psychosocial consequences for the family, and survivorship [22-25]. HNC caregivers have also reported a need for psychological support, self-help groups, assistance with coping strategies, patient care, legal/financial support, and healthcare service assistance [22, 23, 25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, our theory shows that the family plays a "supporting role" in persuading and leading the patient to the surgery. This role emerges from narratives of patients and HCPs and was also confirmed by studies conducted in other contexts (Lang et al, 2013;Rana et al, 2016;Richardson, Morton, & Broadbent, 2015). In a few cases, the interviewed patients spontaneously cited some family members who had evidently played a supporting role in this phase.…”
Section: Research Limitations and Future Developmentssupporting
confidence: 65%
“…Head and neck caregivers may in fact be more distressed by head and neck cancer than the patients themselves (Richardson et al . ,b). Around a third of head and neck cancer relative/friends indicate that they believe that caring is a significant burden on caregivers (Precious et al .…”
Section: Introductionmentioning
confidence: 99%